2021
DOI: 10.21037/atm-20-2159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results and complications associated with oblique lumbar interbody fusion technique

Abstract: Background: Oblique lumbar interbody fusion (OLIF) is a minimally invasive technique performed through the antero-oblique trajectory to address a wide range of lumbar pathologies. However, it can lead to complications. We reviewed the results of OLIF and discussed the effective methods to avoid such complications.Methods: Seventy-nine consecutive patients who underwent OLIF between May 2016 and July 2019 were retrospectively analyzed. They were divided into three groups: stand-alone, posterior, and lateral fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The authors suspected that complications associated with psoas muscle injury in DLIF may have contributed to this difference. Other previous studies have also reported significantly higher rates of anterior thigh symptoms (pain, sensory deficit, and hip flexor weakness) in DLIF (30%–40%) than OLIF (1.3%–21.4%) [ 38 , 60 - 62 ]. However, these symptoms are generally transient and resolve at postoperative 3 to 6 months [ 63 ].…”
Section: Clinical and Radiological Outcomes Of Olifmentioning
confidence: 81%
See 3 more Smart Citations
“…The authors suspected that complications associated with psoas muscle injury in DLIF may have contributed to this difference. Other previous studies have also reported significantly higher rates of anterior thigh symptoms (pain, sensory deficit, and hip flexor weakness) in DLIF (30%–40%) than OLIF (1.3%–21.4%) [ 38 , 60 - 62 ]. However, these symptoms are generally transient and resolve at postoperative 3 to 6 months [ 63 ].…”
Section: Clinical and Radiological Outcomes Of Olifmentioning
confidence: 81%
“…Degenerative disc disease, spinal stenosis, and spondylolisthesis (degenerative and spondylolytic) are common indications for OLIF, and previous studies have reported favorable outcomes following OLIF in these conditions [ 37 , 38 ]. However, there is skepticism among spine surgeons on whether severe lumbar spinal stenosis can be effectively treated by indirect decompression alone [ 39 ].…”
Section: Expanding Indications For Olifmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining the height of the increased intervertebral space and promoting early intervertebral fusion is vital in maintaining the surgical efficacy of OLIF. However, cage subsidence is the most common complication of OLIF, with an incidence of 10.1%-35.3% [2,3]. In addition, subsidence has a negative effect on interbody fusion [4].…”
Section: Introductionmentioning
confidence: 99%